Escola Alegria de Saber: uma escola brasileira no Japão (1995-2011) - Brito, Cláudia Regina de (2012)
This study aims to analyze Brazilian educational institutions located in Japan focusing on the institution Escola Alegria de Saber - EAS, established in 1995. These institutions were established to meet the demands for schooling for the children of Brazilian immigrants, known as dekassegui workers. The investigation revealed the migration process throughout the 20th and 21st centuries, mainly between 1980 and 2009, the period in which occurred the migration process of Nipo-Brazilians to Japan. In order to build the object of study the following goals were pursued: unveiling what led to the establishment of Brazilian educational institutions in Japan; reconstructing the history of the school Escola Alegria de Saber - EAS, understanding its constituent elements; verifying what motivated the Japanese government to draw educational policies which allow flexibility in establishing Brazilian schools, even granting the title of "Miscellaneous school" ; and considering the approval of the reports issued by the National Council of Education, the Ministry of Education in Brazil, validating the educational institutions in Japan This research expands previous studies, in which the Japanese migration to Brazil as cheap labor was investigated. Emphasis was given to the construction of Japanese ethnicity in relation to the surrounding society. The migration developed between these countries was motivated by economic interests, which is defined as a movement marked by departure and return of the same generation and their descendants, in a short period of time. The research examined the migrant´s condition facing adverse situations and social relations which are established and define them as a group. In addition the research concentrated on tracing the group´s similarities in the movements of departure and return, especially regarding the implementation of schools for descendants, which include guidelines and legal requirements from the home country, reinforcing the idea of returning to the country. This study also examined conflicting experiences especially in times of economic crisis when this group is harassed and treated like foreigners or merely as labor. The group has become resilient, tackling the barriers and in reaction use the term gambarê as a symbolic strategy for survival. The research was analyzed in the light of the narrow and inseparable relationship between specific, singular and universal, establishing the mediations between the object of research, within social and historical trends of the dominant social organization, that is, capitalist society. The sources used were obtained in documents, bibliographies and semi-structured interviews, resulting form field work conducted in Japan. The work was completed with the understanding that in Japan, the Nipo Brazilians realize they are different from the Japanese. The opposition between natives and foreigners are build due to social representations which differentiate them. Moreover they perceive themselves as hired labor and the importance in maintaining educational institutions for their descendants, since the Japanese school does not meet everyone´s needs and demands.